Study of Single Stage Compressive Test (SST) Laboratory Determination In Soft Formation Rods with Various Compositions Of Silica and Calcite Impurities In High Pressure and Temperature - Nur Suhascaryo; Ilham Dary Wibowo; Sandika Pratama; Ridwan Hadi S (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2020)
Single Stage Compressive Test is a compressive test tool to study the nature of reservoir rock strength by modeling the reservoir rock into laboratory conditions. Measurement results on surface conditions generally have different results from actual conditions in reservoir conditions, therefore, the working principle of this tool considers the principal stress that works on reservoir rocks designed with the addition of silica and calcite impurities and models reservoir conditions in more detail such as high temperature conditions, the presence of pore pressure and the influence of the presence of fluid in the reservoir rock. Such a laboratory model will provide an overview of the magnitude of the effect of stress, both the maximum stress or the minimum stress acting on the reservoir rock and the effect of temperature and the presence of fluid on the nature of the reservoir rock strength. SST is designed by considering reservoir conditions in Indonesia, generally described as the maximum axial pressure (overbourden pressure) reaching 4000 psia and radial pressure which can act as confining pressure (pore pressure) reaching 1500 psia and the maximum temperature reaching 400 oF. This paper will explain in detail about the design of the SST tool and report the results of the synthetic core compressive test using this tool.